2001
DOI: 10.1136/jms.8.4.183
|View full text |Cite
|
Sign up to set email alerts
|

Cancer screening coverage of south Asian women in Wakefield

Abstract: (J Med Screen 2001;8:183-186)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 2 publications
0
21
1
Order By: Relevance
“…Several population-based studies in the United Kingdom, a country whose health insurance coverage and cancer care system are comparable to those in Canada, revealed particularly low rates of breast, cervical, and colorectal cancer screening among women of sa ancestry 24,27,51 . Szczepura and colleagues 23 compared breast and colorectal cancer screening patterns over time for 5 sa ethnic groups and "non-Asians."…”
Section: Discussionmentioning
confidence: 99%
“…Several population-based studies in the United Kingdom, a country whose health insurance coverage and cancer care system are comparable to those in Canada, revealed particularly low rates of breast, cervical, and colorectal cancer screening among women of sa ancestry 24,27,51 . Szczepura and colleagues 23 compared breast and colorectal cancer screening patterns over time for 5 sa ethnic groups and "non-Asians."…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our findings are similar to those in previous studies reporting that physician recommendation, acculturation and length of stay in the United States, and barriers to mammography were significantly associated with screening behavior. 16,25,37,[77][78][79][80][81][82][83][84] Self-efficacy is a key variable in the Health Belief Model (HBM). Interestingly, self-efficacy was significant in distinguishing between women who had never had a mammogram and those who had had at least one but was not a predictor for adherence to screening guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of ethnic background, there exists a wealth of research on how particular ethnic, cultural or religious groups can hold different understandings of health and illness, and have different experiences of health care. For example, work exists on the different beliefs about, and responses to, hypertensive therapy amongst the white population and those born in the West Indies (Morgan and Watkins, 1988), how culturally defi ned concepts of health and illness can infl uence heart health-associated behaviours (Higginbottom, 2000), the health and illness understandings of African-Caribbeans, and how these may be infl uenced by age and gender (Curtis and Lawson, 2000), the role of culture and religion in how diabetes is managed by Kashmiri men (Naeem, 2003), and how the religious beliefs and customs of Muslim women can impact upon participation in breast and cervical cancer screening (Sutton et al, 2001;Underwood et al, 1999). A look at the population statistics for the area where the research was based showed that the three groups making up the vast majority of the population were white British, south Asian and African-Caribbean.…”
Section: Methodsmentioning
confidence: 99%